Exceptionality in Spanish Stress - Eric Baković (Universitat Autònoma de Barcelona, 2016)
Stress in vowel-final non-verbs in Spanish regularly falls on the penultimate syllable, while stress in consonant-final words regularly falls on the final syllable. There are two main classes of exceptions to this regularity: stress on the syllable preceding the regular one, and stress on the syllable following the regular one. Harris (1983) provides arguments that the second class of exceptions is morphologically systematic, but falls short of the stronger claim that this pattern is simply a subcase of the regular stress pattern. I argue here that there is much to be gained from this stronger claim, including a simple and elegant analysis of the first class of exceptions.